An Experimental Study Investigating the Type of Data Visualizations Used in Infographics on Participant Recall and Information Recognition - Laura Morgan Fischer; Elizabeth Schroeder; Courtney Gibson; Amber McCord; Ginger Orton (Journal of Applied Communications, 2023)
The concept of agricultural sustainability, specifically sustainable beef production, is not well established, and much misinformation frames this conversation. One way agricultural communicators can educate the public on this controversial topic is through infographics. Scholars have suggested recall, or the mental process of retrieving information from the past, as a technique to understand what someone has comprehended when exposed to new information. The Limited Capacity Model of Motivated Mediated Message Processing (LC4MP) provides insight into human information processing and recall, and it guided this study’s development. The purpose of this study was to determine the effect various types of data visualizations used in infographics about agricultural topics have on college students’ knowledge and ability to recall attributes from the data visualizations. An experimental study was conducted where participants viewed one of three infographics with embedded data visualizations and answered questions to understand their recall of information, design elements, and information recognition. The results show pictographs were significantly more effective in participant information recognition and the free and cued recall of design; however, it was not significant for free and cued recall of information. These findings add to the agricultural communication literature as they show how the type of data visualization can impact how viewers encode, store, and retrieve information. The researchers suggest agricultural communicators implement pictographs more frequently in infographic communications strategy. Additionally, agricultural communicators must begin to train students on the use of data visualization techniques in classroom settings.
Keywords: Data Visualization; Infographics; Recall; LC4MP; and Information Recognition